2010
DOI: 10.1167/iovs.09-4873
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Endotoxin-Induced Uveitis in Rats by Plant Sterol Guggulsterone

Abstract: PURPOSE To investigate the anti-inflammatory effects of guggulsterone, an antioxidant and anti-tumor agent, in endotoxin-induced uveitis (EIU) in rats and to elucidate the underlying molecular mechanism(s) related to ocular inflammation. METHODS EIU was induced by subcutaneous injection of lipopolysaccharide (LPS) (150 ug) in Lewis rats treated with guggulsterone (30 mg/kg body wt, i.p) or its carrier. After 24 h the rats were sacrificed, eyes were enucleated and aqueous humors (AqH) were collected. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 37 publications
(49 reference statements)
2
28
0
1
Order By: Relevance
“…8 However, prescription-based use of many of these agents, such as guggulsterone, 60 ethyl pyruvate, 61 lutein, 62 and astazanthin, 63 in humans for the treatment of uveitis has not materialized for various reasons. Prominent reasons that limit their use in humans are lack of toxicity studies, lack of knowledge on safe dosage range, potential toxicity on higher therapeutic dosage, and lack of studies to determine safe delivery methods.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, prescription-based use of many of these agents, such as guggulsterone, 60 ethyl pyruvate, 61 lutein, 62 and astazanthin, 63 in humans for the treatment of uveitis has not materialized for various reasons. Prominent reasons that limit their use in humans are lack of toxicity studies, lack of knowledge on safe dosage range, potential toxicity on higher therapeutic dosage, and lack of studies to determine safe delivery methods.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Proteasomal degradation of the inhibitory factor IjB is necessary for NF-jB activation, and the inhibition of proteasome function theoretically maintains NF-jB in the inactive state in the cytosol and prevents its nuclear translocation. Proteasome inhibition is effective in treating several animal models of autoimmune disease, and to our knowledge our study is the first to demonstrate its antiinflammatory effect in EIU.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have noted that there is increased expression of activated NF-jB associated with EIU, and that the inhibition of NF-jB can halt inflammation. [7][8][9][10][11][12] NFjB is an ubiquitous transcription factor, and it regulates the transcription of a wide range of genes responsible for inflammation, such as cytokines, chemokines, cell-adhesion molecules, and stress-response proteins. 13 Several inflammatory mediators, including interleukin (IL)-1, IL-6, tumor necrosis factor (TNF)-a, interferon (IFN)-c, monocyte chemoattractant protein (MCP)-1, intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1, inducible nitric oxide synthase (iNOS), and cyclo-oxygenase (COX)-2, are increased in animals with EIU and seem to be up-regulated by NF-jB.…”
Section: Methods Eiu Was Induced By Footpad Injection Of Lps Intomentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported that hot water extract of Scutellariae radix may have an inhibitory effect on experimental anterior uveitis induced by lipopolysaccharide (LPS) in pigmented rabbits. Berberine from Berberis aristata ( daaru haridra in Ayurveda), plant sterol guggulsterone, polyphenols from Lonicera caerulea L. and Aronia extract, anthocyanins from Vaccinium myrtillus L., and Gingko biloba have exhibited potent anti-infl ammatory activity against endotoxin-induced uveitis in vivo (Kalariya et al 2010 ;Jin et al 2006 ;Ohgami et al 2005 ;Yao et al 2010 ). Plant pigments such as, fucoxanthin, lutein, and Lycium have been reported to show protection against LPS-induced uveitis; however further investigations elucidating the working mechanism are anticipated.…”
Section: Plant-derived Compounds For Uveitismentioning
confidence: 99%